Digital biomarkers and artificial intelligence: a new frontier in personalized management of inflammatory bowel disease - De Deo, Diletta; Dal Buono, Arianna; Gabbiadini, Roberto; Nardone, Olga Maria; Ferreiro-Iglesias, Rocio; Privitera, Giuseppe; Bonifacio, Cristiana; Barreiro-de Acosta, Manuel; Bezzio, Cristina; Armuzzi, Alessandro (Frontiers in Immunology, 2025)
Background and aimsArtificial intelligence (AI) is rapidly gaining traction in gastroenterology, particularly in the management of inflammatory bowel disease (IBD). Given the complexity of IBD care, AI offers the potential to enhance diagnosis, monitoring, and treatment. This review aims to summarize recent developments in AI applications for IBD and identify key challenges and opportunities for future research and clinical implementation.MethodsA narrative literature review was conducted, incorporating recent studies utilizing AI —including machine learning (ML) and deep learning (DL) — across various aspects of IBD care.ResultsAI has demonstrated utility in multiple domains of IBD management, including endoscopic disease activity assessment, histological evaluation, imaging interpretation, prediction of disease course, treatment response, and real-world data integration. Despite promising accuracy and utility, most models remain in early development stages and lack widespread clinical validation. Major barriers include data heterogeneity, limited generalizability, and regulatory uncertainties.ConclusionAI has significant potential to revolutionize IBD care. Continued multidisciplinary collaboration, validation in diverse clinical settings, and integration into clinical workflows are critical for realizing its full impact.